OpenGL : build high performance graphics : assimilate the ideas shared in the course to utilize the power of OpenGL for performing a wide variety of tasks : a course in three modules.: build high performance graphics : assimilate the ideas shared in the course to utilize the power of OpenGL for performing a wide variety of tasks : a course in three modules. (2017) - Movania, Muhammad Mobeen; Lo, William C. Y; Wolff, David; Lo, Raymond C. H
No abstract available